A Very Rare Cause of Lower Limb Ischemia in Young People: Popliteal Artery Entrapment - Altinsoy, Hasan Baki (Open Cardiovasc Med J, 2018)
BACKGROUND: Popliteal artery entrapment syndrome (PAES) is a very rare pathology that can cause lower extremity ischemia in healthy young people. Anomalous anatomic relationships between the popliteal artery (PA) and the surrounding musculo-tendinous structures cause PAES. We present 31 patients with PAES in 35 limbs that were treated surgically in our clinic within a 12-year period. PATIENTS AND METHODS: From 2001 to 2015, 31 patients (mean age: 32 ± 7.4 years) underwent surgery for PAES. ; 4 patients presented had bilateral PAES. Doppler ultrasonography (US), magnetic resonance angiography (MRA), and conventional angiography were performed as diagnostic procedures. We detected Type I PAES in 4 limbs and Type II PAES in 12 limbs. In the remaining 19 limbs, we diagnosed Type III or Type IV PAES. Simple release of the PA, PA embolectomy and simple release, and the radial artery (RA) patch angioplasty, with or without thromboendarterectomy (TEA), were performed. In 12 limbs, PA continuity was provided by RA interposition. RESULTS: With the exception of 5 patients, no complications were seen after surgery. Haematoma was detected in 2 patients and local infection in 2 patients. One patient required a revision for recurrent PA thromboembolic event 12 h after surgery. At a median follow- up of 23 months (range: 11-29 months), there were no postoperative complications. CONCLUSIONS: PAES can result in lower limb ischemia due to chronic vascular trauma in young healthy patients. The use of diagnostic tools such as US, a non-invasive method, and MRA are effective diagnostic tools for early diagnosis. With their combined approach, exact and early diagnosis can be achieved. PA release, alone or with arterial bypass using RA, is a viable treatment option when intervention is necessary to prevent limb loss in the early stages of the disease.